O atendimento educacional especializado no processo de inclusão escolar, na rede municipal de ensino de Mossoró/RN - Bedaque, Selma Andrade de Paula (2012)
This dissertation aims to analyze the specialized educational services(AEE, Portuguese) implemented in four municipal schools of Mossoró/RN, with attention to the process of collaboration between regular classroom teachers and multifunctional resource classroom teachers. We use as theoretical reference the works of Vygotsky and others authors that write about education and collaboration. To accomplish the research we chose a qualitative approach, using as a methodological resources: study of cases, bibliographical, documental and field research. For the field research we make observations in regular and multifunctional classrooms. We produce group intervieus with regular and multifunctional teachers. From the analysis performed we identify that the concepts and the practices of teachers in regular classrooms changes, with integrationist predominance. The AEE s teachers had more inclusive conceptions and greater investment in continuing education than the regular classroom teachers. The practices of regular classroom teachers are more traditional, what makes the learning process more difficult for the students, even more for the students with disabilities and pervasive developmental disorders. Teachers of AEE was more interactive and creative, however, the attention to the students was more individual. In three of the four schools surveyed stand out the efforts of the teachers of specialist classroom to collaborate with regular school teachers, by notes, e-mails, phone calls and resource sharing. In one of the four was noted a good collaborative interactive between the AEE teachers and the regular school teachers. The school with the worst improvement was that in which the actions of the teachers of the AEE were limited to actions in multifunctional resource classroom. The resistance to these professionals was identified in the statements of the regular classroom teachers. Another issue raised was the lack of time for teachers to conduct AEE actions that contribute to the process of school students, because their working hours is restricted to the opposite turn in school. Transport difficulties for the students to attend the resource classroom multifunctional and the lack of dialogue with the health sector was challenges for the four schools. The families were with a practically constant interest to interact with the AEE teachers in the four schools. Thus, we believe that the presence of AEE school can make contributions to the educational process, however, it is necessary more attention to the collaborative process between teachers and the school community